Growth performance of Cirrhinus mrigala (Ham.) fingerlings maintained on mixed feeding schedule of diets having different protein content - Saroha, R P; Garg, S K (Indian Journal of Fisheries, 2011)
Seven different mixed feeding schedules were evaluated in Cirrhinus mrigala fingerlings having mean body weight (BW) of 2.84g employing a low (L) protein (20.29%) diet and a high (H) protein (40.12%) diet, feeding @ 3% Bwd-1 for 45 days. Regular feeding for 45 days on low protein (L) diet resulted in significantly (P<0.05) low growth and low protein efficiency ratio (PER), while feeding on 1L/3H feeding schedule resulted in good growth performance equivalent to the fish fed continuously on high protein diet. Gross protein retention (GPR), Gross energy retention (GER), Apparent nutrient digestibility (APD) and Feed conversion ratio (FCR) were similar in fingerlings fed either continuously on high protein diet or on a feeding schedule consisting of 1L/3H, while, PER values were significantly (P<0.05) high in fingerlings fed on 1L/3H diet in comparison with fish fed continuously on high protein diet. Based on total protein input, 12.36% protein can be saved without affecting growth by adopting the 1L/3H feeding schedule as compared to feeding the fish daily on high protein diet.